The Impact and Reflection of Vulgar and Ugly Acts in Live Streaming - Song, Mufan (Transactions on Economics, Business and Management Research, 2024)
This paper examines the proliferation of vulgar live streaming content on platforms like Douyin and TikTok, focusing on its impacts on individual viewers and societal values. Through case studies of two female anchors, it explores the motivations behind creating such content, audience characteristics, and the resulting consequences. The study recommends enhancing content regulations, fostering viewer discernment, and implementing policies to curb the spread of vulgar content, thereby promoting a healthier online environment.